2010
DOI: 10.1080/10615800802609965
|View full text |Cite
|
Sign up to set email alerts
|

How obstacles and facilitators predict academic performance: the mediating role of study burnout and engagement

Abstract: Most people would agree with the maxim that "success breeds success". However, this is not the whole story. The current study investigates the additional impact of psychosocial factors (i.e., performance obstacles and facilitators) as well as psychological well-being (i.e., burnout and engagement) on success (i.e., academic performance). More specifically, our purpose is to show that, instead of directly affecting future performance, obstacles and facilitators exert an indirect effect via student well-being. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
257
4
55

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(382 citation statements)
references
References 44 publications
20
257
4
55
Order By: Relevance
“…on the contrary, both teachers and fellow colleagues can help prevent and counteract the development of burnout through positive motivation and encouragement. salmela-aro, Kiuru, Pietikäinen, and Jokela (2008), in a study with Finnish students, observed that positive motivation received from teachers was negatively related to school-related burnout. Personal efficacy has been pointed out as a consequence of burnout, and a personality factor rather than a dimension of burnout (shirom & ezrachi, 2003).…”
Section: Second-order Student Burnout Factormentioning
confidence: 99%
“…on the contrary, both teachers and fellow colleagues can help prevent and counteract the development of burnout through positive motivation and encouragement. salmela-aro, Kiuru, Pietikäinen, and Jokela (2008), in a study with Finnish students, observed that positive motivation received from teachers was negatively related to school-related burnout. Personal efficacy has been pointed out as a consequence of burnout, and a personality factor rather than a dimension of burnout (shirom & ezrachi, 2003).…”
Section: Second-order Student Burnout Factormentioning
confidence: 99%
“…Carlotto and Câmara (2006), Dyrbye et al (2010), Martinez et al (2000 and Salanova, Schaufeli, Martinez, and Breso (2010) and emphasize that early detection of symptomatic significant levels of burnout can be an indicator of potential problems, in both school and professional contexts, enabling preventive interventions. Marôco and Tecedeiro (2009) also indicate that the occurrence of Burnout can seriously limit students psychosocial wellbeing and the academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, higher education students have been identified in the literature as a vulnerable group for the development of Burnout (Balogun, Helgemoe, Pellegrini, & Hoeberlein, 1995;Marôco & Tecedeiro, 2009;Marôco, Tecedeiro, Martins, & Meireles, 2008;Martinez, Pinto, & Silva, 2000;Schaufeli, Martinez, Pinto, Salanova, & Bakker, 2002) due to socio-economic pressures, concerns about their professional future, relationships with peers and teachers, tests and papers to which they are constantly exposed, and therefore constitute a risk population to be studied. Carlotto and Câmara (2006), Dyrbye et al (2010), Martinez et al (2000) and Salanova, Schaufeli, Martinez, and Breso (2010) and emphasize that early detection of symptomatic significant levels of burnout can be an indicator of potential problems, in both school and professional contexts, enabling preventive interventions. Marôco and Tecedeiro (2009) also indicate that the occurrence of Burnout can seriously limit students psychosocial wellbeing and the academic performance.…”
mentioning
confidence: 99%
“…Schaufeli et al have developed a student version of the Maslach Burnout Inventory (MBI-SS) (Schaufeli et al 2002). Many studies have used this scale to examine student's burnout levels (Esteve, 2003;Breso et al, 2010;Gan and Shang, 2007;Hu and Schaufeli, 2009;Jia et al, 2009;Lee et al 2010;Lingard, 2007;Morgan, B., 2008;Zhang et al 2007;Salanova et al, 2009).…”
Section: Introductionmentioning
confidence: 99%